Unveiling the shield: decoding UPSIDE®-induced biochemical responses against Botrytis cinerea in grapevine - Scimone, Giulia; Mariotti, Lorenzo; Gelová, Zuzana; Milanollo, Lisa; Pisuttu, Claudia; Pellegrini, Elisa; Nali, Cristina (Frontiers in Plant Science, 2025)
Botrytis cinerea Pers. is one of the major threats to grapevine, causing substantial losses in both yield and fruit quality. In light of the evolving regulatory frameworks and growing concerns over the use of chemical fungicides, the search for new green and affordable tools has become increasingly relevant. This study aims to investigate biochemical changes on grapevine induced by the application of UPSIDE® (U), a new yeast-based product developed for organic viticulture. Foliar spray applications of U were carried out once a week for three consecutive weeks on potted grapevines (U+), while other plants were sprayed with sterile water (U-). At the end of the treatments, half plants from each group were B. cinerea (Bc+)- or mock-inoculated (Bc-). Fully expanded leaves were sampled at 24 hours after each spray, and at 0-, 1-, 3-, 24- and 48-hours post inoculation (hpi), and then used for biochemical analysis and microscopic observations. In U+/Bc- plants, hydrogen peroxide levels increased at all analysis times (+50% on average), along with a 3-fold rise in ethylene/jasmonic acid (Et/JA) ratio at 3 hpi, in comparison to U-/Bc-. In U-/Bc+ plants, the Et/JA ratio remained high throughout the experiment, peaking at 48 hpi, while salicylic acid (SA) dropped at 1 hpi (more than 7-fold and –42%, respectively, compared to U-/Bc- ones). Similarly, U+/Bc+ plants showed increased levels of Et/JA ratio from 3 to 48 hpi and abscisic acid at 3 hpi (5- and 16-fold, respectively, compared to U-/Bc-), with a SA decrease at 1 hpi (–63%, in comparison to U-/Bc-). Microscopic observations revealed fully hyphal spread on U-/Bc+ leaves, while U+/Bc+ showed only slightly formed and misshaped germ tubes. Results confirmed the potential of U in triggering plant defense responses, thus protecting grapevine leaves against Bc.